SPIRITUALITAS DAN KEKUASAAN DALAM LAKON WAYANG ARJUNAWIWAHA KARYA KI NARTOSABDO: ANALISIS WACANA KRITIS MICHEL FOUCAULT - Aris Aryanto; NFN Rochimansyah; Khabib Sholeh; Herlina Setyowati (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2021)
The Arjunawiwaha puppet play does not only convey discourse on Arjuna’s attempt to meditate on Mount Indrakila, but there is an ulterior motive behind it. Therefore, the purpose of this study is to describe the hidden motives contained in the Arjunawiwaha puppet play by Ki Nartosabdo. This research includes literary research in the form of qualitative descriptive with collection techniques, namely content analysis. Michel Foucault's theory of knowledge power discourse is applied in this study to see the implicit motives in the Arjunawiwaha story. In his hermitage, Arjuna received two divine gifts, first, the Pandavas would excel in the great war of Bharatayuda and the Pandavas would become rulers in the country of Astina; second, Arjuna received the gift of Batara Guru in the form of an arrow named Kyai Pasupati. The hidden motive in the Arjunawiwaha puppet play is due to the basic human psychic impulses that the researcher identifies as the motive for power hiding in the motive of spirituality. Arjuna's naivety who only asked for victory for the Pandavas had to be paid handsomely by the death of the Pandava children on the battlefield. Arjunawiwaha puppet plays can provide moral teaching on the importance of self-control in relation to the human ego or will.Lakon wayang Arjunawiwaha tidak sekadar menyampaikan wacana tentang usaha Arjuna melakukan tapa di Gunung Indrakila, tetapi ada motif tersembunyi dibaliknya. Oleh karena itu, tujuan penelitian ini untuk mendeskripsikan motif tersembunyi yang terdapat dalam lakon wayang Arjunawiwaha karya Ki Nartosabdo. Penelitian ini termasuk penelitian sastra berbentuk kualitatif deskriptif dengan teknik pengumpulan data, yaitu kajian isi. Teori wacana kuasa pengetahuan Michel Foucault diterapkan dalam penelitian ini untuk melihat motif tersirat dalam cerita Arjunawiwaha. Dalam pertapaannya, Arjuna mendapat dua anugerah dewa, pertama, Pandawa akan unggul dalam perang besar Bharatayuda dan Para Pandawa akan menjadi penguasa di negara Astina; kedua, Arjuna mendapatkan anugerah Batara Guru berupa anak panah bernama Kyai Pasupati. Motif tersembunyi dalam lakon wayang Arjunawiwaha karena adanya dorongan dasar psikis manusia yang dapat ditengarai sebagai motif kekuasaan yang bersembunyi dalam motif spiritualitas. Kenaifan Arjuna yang hanya meminta kemenangan bagi Pandawa harus dibayar mahal dengan kematian anak-anak Pandawa di medan Perang. Lakon wayang Arjunawiwaha dapat memberikan pengajaran moral tentang pentingnya pengendalian diri kaitannya dengan ego atau kehendak manusia.